Experimental and modelling study of ammonium based ionic liquids in the absence and presence of methanol for CO2 hydrates - Ul Haq, I. (Elsevier B.V., 2022)
The thermodynamic hydrate inhibition behavior of two ammonium based ionic liquids (AIL), namely tetra methyl ammonium tetrafluoroborate (TMABF4) and tetraethyl ammonium tetrafluoroborate (TEABF4) and their mixtures with methanol for CO2 hydrates is significant to study. The Hydrate Liquid Vapor Equilibrium (HLVE) values for CO2 hydrates are determined using the T-cycle method in the pressure range of 2.0 to 3.4 MPa at 5 and 10 wt solution concentrations. For the studied systems, the inhibition effect including average suppression temperature (Å¦) and dissociation enthalpies (Hdiss), are determined. TMABF4 in pure as well as in mixture with methanol showed higher thermodynamic hydrate inhibition effect in comparison with TEABF4. The average suppression temperature values for TMABF4 and TMABF4 + methanol are 0.90 K and 3.81 K respectively at 10 wt concentration. In addition, Dickens and Quinby Hunt model is utilized for the prediction of CO2 hydrate liquid vapor equilibrium. The modelling results match well with the experimental data. The employment of these chemicals in the thermodynamic inhibition of CO2 hydrates systems may lead to their usage in the field of flow assurance as they exhibited hydrate inhibition effect. Â© 2021 Elsevier B.V.